Pengaruh Pelaksanaan Wirid Remaja terhadap Pembentukan Akhlakul Karimah di SMAN 2 Sungai Limau - Kusumawati, Arnim; Saputra, Edi (YASIN, 2025)
This study is motivated by the weak application of religious values in students’ daily lives, as reflected in a lack of respect for parents, teachers, and peers, as well as low environmental awareness. One effort to foster moral development is through the wirid remaja program. The purpose of this research is to determine the effect of wirid remaja implementation on the akhlakul karimah (noble character) of students at SMAN 2 Sungai Limau. Wirid remaja is a bi-monthly activity that includes congregational zuhr prayer, dhikr, istighasah, supplication, and thematic sermons tailored to moral development needs. A quantitative method with a correlational design and simple linear regression analysis was used. The sample consisted of 82 Grade X and XI students selected through simple random sampling from a total population of 416. Research instruments included questionnaires measuring wirid remaja (X) and akhlakul karimah (Y), with data analysis covering normality, linearity, and hypothesis testing using SPSS version 20. The findings show a significant influence of wirid remaja on students’ moral character, with a calculated t-value (0.0329) exceeding the critical t-value (0.03008), and a significance level of 0.003 < 0.005. Although the correlation is relatively low (r = 0.329), the wirid remaja program has been proven to contribute to character formation. These results highlight the importance of sustained involvement from Islamic Education and Character Education teachers in supervising and developing wirid remaja as a strategic component of character education.